2017
DOI: 10.3892/etm.2017.5413
|View full text |Cite
|
Sign up to set email alerts
|

Clinical manifestations and epigenetic mechanisms of gastric mucosa associated lymphoid tissue lymphoma and long‑term follow‑up following Helicobacter�pylori eradication

Abstract: Abstract. The current study aimed to summarize the clinical manifestations and identify the epigenetic mechanisms of gastric mucosa associated lymphoid tissue (MALT) lymphoma, as well as evaluate the long-term effects of Helicobacter pylori (H. pylori) eradication. A total of 122 patients with marginal zone B-cell lymphoma of primary gastric MALT lymphoma were enrolled in the present study. The clinical manifestations of gastric MALT lymphoma, including symptoms, H. pylori state and endoscopic type, were summa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
16
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 11 publications
(16 citation statements)
references
References 33 publications
0
16
0
Order By: Relevance
“…The underlying mechanism of miR-197-3p downregulation induced by the overexpression of hsa_circ_0092306 needs to be revealed in future studies. In addition, according to the Circular RNA Interactome website, apart from the miR-197-3p, the tumor suppressors miR-198 32 and miR-383 33 also show a high context with the hsa_circ_0092306 binding score. Similarly, miR-197-3p targets many genes predicted by TargetScan in addition to PRKCB.…”
Section: Discussionmentioning
confidence: 99%
“…The underlying mechanism of miR-197-3p downregulation induced by the overexpression of hsa_circ_0092306 needs to be revealed in future studies. In addition, according to the Circular RNA Interactome website, apart from the miR-197-3p, the tumor suppressors miR-198 32 and miR-383 33 also show a high context with the hsa_circ_0092306 binding score. Similarly, miR-197-3p targets many genes predicted by TargetScan in addition to PRKCB.…”
Section: Discussionmentioning
confidence: 99%
“…Ulcers are the most common etiology of upper GI bleeding (59%), compared to malignancies (2–4%) [1]. Gastric MALT lymphoma has been reported to manifest as upper GI bleeding upon diagnosis in only 15.6% of the cases [4]. The presentation of massive bleeding with hypovolemic shock is very rare as the first sign of gastric MALT lymphoma, especially in an early stage – in this case, stage IE.…”
Section: Discussionmentioning
confidence: 99%
“…Complete remission was achieved in 74.4% of patients who underwent eradication therapy, after a median time of around 4 months. A study showed that the 3-year and 5-year survival rates were 90.3 and 76.2%, respectively [4]. Even after remission, relapse and reinfection with H. pylori should be monitored, as well as the risk of gastric adenocarcinoma, because the risk is 6-fold increased in patients with gastric MALT compared to the general population [15].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations